Improving Creative Thinking Skill with Linear Equation Worksheet Based on Tri-N Activity - Fitria Sulistyowati; Sri Adi Widodo; Maria Marfiani Tapo; Wikan budi Utami; Benjamin Laurentino Vaz (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2026)
Tri-N or Niteni, Nirokake, Nambahi (observing, imitating, adding) is a learning approach initiated by the Father of Indonesian Education, Ki Hadjar Dewantara. Tri-N is an adaptable approach that is easy to apply in every learning material, including mathematics. This research and development aims to develop an e-worksheet based on Tri-N for system of linear equations in two variables to improve junior high school students' creative thinking skills using the Liveworksheet Platform. The study employed the ADDIE development model, with stages: analysis, design, development, implementation, and evaluation although it was limited to the development stage to focus on validity and practicality. The results of this research include: (1) an e-worksheet based on Tri-N in a two-variable linear equation system has been produced to improve the creative thinking skills of junior high school students, (2) the validity test of the e-worksheet developed shows that 98.60% is categorized as very valid, and (3) the practicality test of the e-worksheet shows that 67.14% of students strongly agree and 31.90% of students agree on each aspect of the assessment. So, it can be concluded that e-worksheet based on Tri-N in a two-variable linear equation system is valid and practical for improving junior high school students' creative thinking skills. It is hoped that the research can become a reference in further research to test the effectiveness of the e-worksheet.